Visualisasi Hasil Pemilu 2019 Berbasis Webgis di Kelurahan Koto Panjang Ikua Koto - Putri, Ramona Zeka; Yulfa, Arie (Lembaga Yasin AlSys, 2024)
The data from the 2019 legislative election in Padang City is important and can be used by various groups. This data can serve as material for eval_uating the implementation of the 2019 legislative election in Padang City and as a projection for future elections. However, the data from the 2019 legislative election in Padang City that is circulating is only in file form and only includes the number of votes for each party and candidate within the village and polling station (TPS) areas. This makes it difficult to analyze the vote distribution for each party in areas smaller than a village but larger than a TPS, specifically at the RW level. The type of research used in this study is Research and Development (R&D) with the Systems Development Life Cycle (SDLC) methodology using a prototype development model. By utilizing a Content Management System (CMS) in the open-source WordPress application, this research aims to build a dynamic website. The result of the research is a WebGIS that visually presents information, such as an interactive map displaying the results of the political parties' votes. It includes table displays, jpg previews, and pie charts. The WebGIS hasilpemilukpik has five main menus: login, home, map, data, and about. The development of the WebGIS (dev-hasilpemilukpik.pantheonsite.io) has undergone product testing, and respondents overall have responded positively to the functionality and appearance of the WebGIS.